Maternal exposure to ambient cadmium levels, maternal smoking during pregnancy, and congenital diaphragmatic hernia. Issue 18 (23rd July 2019) - Ramakrishnan, Rema; Stuart, Amy L.; Salemi, Jason L.; Chen, Henian; O'Rourke, Kathleen; Kirby, Russell S.
Abstract: Background: Congenital diaphragmatic hernia (CDH) is a rare musculoskeletal birth defect with a prevalence of 2.61 per 10, 000 in the United States. There is limited evidence for ambient air pollutants in the etiology of CDH in humans. Objectives: We investigated the role of maternal exposure to ambient cadmium as a risk factor for CDH (overall and stratified by isolated and non‐isolated subtypes) in Florida and whether maternal smoking during pregnancy was an effect modifier of this association. Methods: We conducted a population‐based, retrospective cohort study using data from the 1999–2012 Florida Birth Defects Registry linked to the National Air Toxic Assessment database. Analyses included chi–square tests; multilevel Poisson regression models to calculate measures of association between cadmium and CDH; and stratified analyses to examine effect modification by maternal smoking status. Results: The study population consisted of 2, 591, 395 live births including 840 CDH cases. We did not find evidence for an association between maternal exposure to ambient cadmium concentration and CDH. We observed a 24% increased risk of CDH among isolated cases in the highest quartile of cadmium exposure (95% confidence interval [CI]: 1.00, 1.55). Although we were limited by small sample size for CDH cases, we found that among mothers who smoked during pregnancy, exposure to the highest quartile of cadmium was associated with more than two times higher risk for CDH among overall (95%CI: 1.04, 4.39) and isolated (95%CI: 1.07, 5.57) cases. Conclusions: Additional research is needed to elucidate the mechanism by which maternal ambient cadmium exposure may increase the risk of CDH in offspring, and the extent to which maternal smoking during pregnancy modifies this association.